Self-assembled nanostructures of phosphomolybdate, nucleobase and metal ions synthesis and their in vitro cytotoxicity studies on cancer cell lines. Issue 48 (16th November 2020) - Chhipa, Hemraj; Srinivasa Reddy, T.; Soni, Sarvesh K.; Selvakannan, PR.; Bhargava, Suresh K.
Abstract : The ability of multidentate nucleobases to coordinate polyoxometalate and metal ions leading to the formation of self-assembled nanostructures has been demonstrated to exhibit enhanced anti-tumor efficiency. Abstract : The ability of the multidentate nucleobases, adenine and thymine, to coordinate polyoxometalate and metal ions leading to the formation of self-assembled nanostructures and their strong cytotoxicity toward cancer cell lines have been demonstrated. A unique synthetic approach is developed to make a series of functional nanoscale hybrid materials consisting of nucleobases (adenine and thymine) and phosphomolybdic acid (PMA) through solid state chemical reaction and self-assembly process. Adenine was protonated through its ring nitrogen, while the ketone group in thymine was protonated during the addition of PMA to these nucleobases. The self-assembled nanostructures formed as a result of the electrostatic interaction between the protonated nucleobases and polyanionic PMA. To promote the base pairing between the nucleobases, chloroaurate ions and silver ions were added to each PMA/adenine and PMA/thymine nanostructures. The complexation between the nucleobases and the added metal ions was found to drive the formation of subsequent self-assembled nanostructures. All the materials were screened for their anticancer activity against breast (MDAMB-231) and prostate (PC-3) cancer cells, and non-cancerous keratinocyte cells HaCaT. PMA/adenine/[AuCl4 ] − and PMA/thymine/Ag + nanostructures were found to have strong anti-cancer activity, while PMA/adenine/Ag +, PMA/thymine/[AuCl4 ] −, and PMA/pdenine, PMA/thymine nanostructures did not exhibit such activity. The unique redox properties of these materials and the self-assembly of the PMA and metal ions were the major factors responsible for the cytotoxicity. This unique approach of making functional nanomaterials incorporate the nucleobase, PMA and metal ions using solid state self-assembly and their anti-cancer applications are considered to be an effective approach for the development of inorganic nucleoside analogue bio-pharmaceutical agents.